“Weekdays in hell” – the materiality of Stalag 318/VIII F (344) Lamsdorf - Kobiałka, Dawid; Tomczak, Sonia; Kaski, Kamil; Pawleta, Michał; Rezler-Wasielewska, Violetta; Stanek, Piotr; Wroniecki, Piotr; Michalski, Marek; Kostyrko, Mikołaj; Lokś, Adam (Archaeologia Historica Polona, 2025)
The Site of National Remembrance in Łambinowice, Poland, is a complex of former prisoner of war (PoW) and resettlement camps that functioned in the vicinity of the village from the time of the Franco-Prussian War in 1870-1871 until 1946. This article focuses on the material remains and landscape transformations related to the functioning of Stalag 318/VIII F (344) Lamsdorf. The authors present the applied methodology of the “Science for society, society for science at the Site of National Remembrance in Łambinowice” project, in which available archival sources and obtained archaeological data complement each other. Such a holistic approach has allowed conducting a more complete inventory and mapping of what has remained of Stalag 318/VIII F (344) Lamsdorf until the present day.